Construction law - Ali Mohamed, Ashgar Ali; Venugopal, A. Vijayalakshmi; Ahmad, Muhamad Hassan (LexisNexis Malaysia Sdn Bhd, 2025)
The word ‘construction’ is commonly used and understood in both technical and generic senses. In the generic sense, ‘construction’ has a broad meaning that applies to the act or process of creating or building something. It can refer to the assembly, formation, or development of physical structures, systems or entities. The term is not limited to a specific industry and can be used in various contexts to describe the organised efforts of bringing elements together to create a tangible result. In the technical sense, construction refers to the process of systematically and methodologically building, assembling, or erecting structures or infrastructure. It involves the use of engineering principles, architectural designs, and project management techniques to ensure the successful realisation of a planned project. The technical aspects of construction encompass a wide range of activities, including site preparation, foundation work, structural framing, system installation, and finishing details, all conducted with adherence to safety standards and applicable regulations. Thus, construction is a process in which site preparation, foundation work, structural framing, system installation, and finishing details are ensured with adherence to safety standards and applicable regulations. Construction contract serves as a road map, fostering clarity and collaboration to achieve the desirable goal of the project. The key elements of a construction contract consist of project specifications, scope of work, schedule, cost, payment terms, quality standards, and dispute resolution mechanisms. The ultimate is to provide a clear framework for the successful completion of the construction project with avoidance or minimising conflict and legal issues. Having said the above, this chapter discusses the applicable laws to the construction industry and the mechanisms for dispute settlements emanating from a concluded construction contract.